SOSIALISASI PENGARSIPAN BAGI WIRAUSAHA DI KAWASAN RW 08 SUNTER AGUNG JAKARTA UTARA - Fakhrur Reza; Koerniawan Hidajat (Jurnal Abdimas Bina Bangsa, 2024)
The reason for conducting this research refers to empirical data from the community as entrepreneurs in RW 08 Sunter Agung, many of whom do not archive even though archiving is important for a businessman/entrepreneur. The method used is direct socialization. The results of this research are: the main material presented in the socialization of archiving for the community as entrepreneurs in the RW. 08 Sunter Agung is an explanation of problems that are at risk for entrepreneurs, the relationship between problems that arise in entrepreneurial activities and archiving activities, namely making it easier and faster to find important past data, archiving activities are a reflection of developing human resources, and saving important documents from possible damaged by natural and human factors. The effectiveness of archiving socialization activities for entrepreneurs in the RW 08 Sunter Agung area, North Jakarta is measured by two indicators, namely the number of targets determined to attend the socialization and the impression of enthusiasm and activity as evidenced by the realization of two-way communication as well as questions and answers and sharing related to archiving socialization and then concluded. The community as entrepreneurs in the RW 08 Sunter Agung area is interested and considers it important to carry out archiving activities for all entrepreneurial activities carried out